Repetitive Detection of Aromatic Hydrocarbon Contaminants with Bioluminescent Bioreporters Attached on Tapered Optical Fiber Elements - Zajíc, Jakub; Ripp, Steven; Trögl, Josef; Kuncová, Gabriela; Pospíšilová, Marie (Sensors (Basel, Switzerland), 2020)
In this study, we show the repetitive detection of toluene on a tapered optical fiber element (OFE) with an attached layer of Pseudomonas putida TVA8 bioluminescent bioreporters. The bioluminescent cell layer was attached on polished quartz modified with (3-aminopropyl)triethoxysilane (APTES). The repeatability of the preparation of the optical probe and its use was demonstrated with five differently shaped OFEs. The intensity of measured bioluminescence was minimally influenced by the OFE shape, possessing transmittances between 1.41% and 5.00%. OFE probes layered with P. putida TVA8 were used to monitor liquid toluene over a two-week period. It was demonstrated that OFE probes layered with positively induced P. putida TVA8 bioreporters were reliable detectors of toluene. A toluene concentration of 26.5 mg/L was detected after <30 min after immersion of the probe in the toluene solution. Additional experiments also immobilized constitutively bioluminescent cells of E. coli 652T7, on OFEs with polyethyleneimine (PEI). These OFEs were repetitively induced with Lauria-Bertani (LB) nutrient medium. Bioluminescence appeared 15 minutes after immersion of the OFE in LB. A change in pH from 7 to 6 resulted in a decrease in bioluminescence that was not restored following additional nutrient inductions at pH 7. The E. coli 652T7 OFE probe was therefore sensitive to negative influences but could not be repetitively used.
Keywords: bioluminescent bioreporter; toluene; Toluene; Hydrocarbons, Aromatic; Pseudomonas putida TVA8; Escherichia coli; Escherichia coli 652T7; toluen; Pseudomonas putida; Optical Fibers; optical fiber biosensor; aromatické uhlovodíky; Biosensing Techniques; Luminescent Measurements; whole-cell biosensor; biosenzitivní techniky; luminiscenční měření; optická vlákna